Использование сетевого протокола ТСР для обмена информацией с электронными аппаратами - Лысенков, Н. А.; Манушин, И. Н.; Рудавин, Е. В. (ХНУРЭ, 2008)
The given work examines questions, related to realization of exchange information and management an electronic vehicle on a local network. For the interface of electronic vehicle and computer on a local network is used ТСР (Transmission Control Protocol ) protocol which provides the best fast-acting and more high reliability of connection, with using of those vehicle facilities, what IP (Internet Protocol) protocol.
Keywords: local network